Anatomy and physiology : the fundamentals - Rizzo, Donald C. (Andover, Mass. : Delmar Cengage Learning, 2012)
A text designed for learners in the allied health field with little or no prior biology or anatomy and physiology knowledge.
The human body -- The chemistry of life -- Cell structure -- Cellular metabolism and reproduction: mitosis and meiosis -- Tissues -- The integumentary system -- The skeletal system -- The articular system -- The muscular system -- The nervous system: introduction, spinal cord, and spinal nerves -- The nervous system: the brain, cranial nerves, autonomic nervous system, and the special senses -- The endocrine system -- The blood -- The cardiovascular system -- The lymphatic system -- Nutrition and the digestive system -- The respiratory system -- The urinary system -- The reproductive system.
Includes index.
Keywords: HUMAN ANATOMY